ENHANCING CRITICAL THINKING IN FIQH LEARNING: THE ROLE OF STRATEGIES AND MEDIA INTEGRATION IN ISLAMIC HIGHER EDUCATION - Saiful Jazil; Ahmad Zahro; Bassam Abul A'la; Moh. Rifqi Rahman; Muh. Sholihuddin; Syamsun Ni’am; Anin Nurhayati (Malaysian Journal of Learning and Instruction)
Purpose – Fiqh learning has traditionally focused on cognitive aspects, such as recalling concepts or matching problems with answers in classical texts. Consequently, it has often neglected the cultivation of learners' critical thinking skills. This study aims to analyze students’ critical thinking practices in fiqh learning, explore the instructional strategies employed, and identify the types of technology used in fiqh learning activities. Additionally, it investigates the continuity between critical thinking, learning strategies, and technology in the context of fiqh education.